Structures of Complexes of Gossypol with Ferrous Sulfate Based on High‐Performance Liquid Chromatography Separation, Spectroscopic Analysis, and PM3 calculations. Issue 19 (17th May 2019) - Zhang, Jian; Ran, Han; Xiong, Wei; Yang, Tianyi; Mei, Yunjun; He, Dongping; Liu, Ye; Cheng, Qunpeng; Li, Shenglan; Song, Guangsen
Abstract: The complexes of gossypol with Fe 2+ were prepared by using methanol as solvent in the presence of CO2 atmosphere. The results from FT‐IR spectra analysis indicated that the aromatic aldehyde groups in gossypol molecules were entirely involved in coordination with Fe 2+ . UV‐Vis absorption spectrum of the complexes in methanol solution displays blue‐shift in comparison with that of gossypol. Five compounds from the complexes were isolated by high performance liquid chromatography. The structures of the complexes are consistent with PM3 calculations. Two compounds were formed by coordination of gossypol with Fe 2+ at 1:2 molar ratio, other three compounds were formed by chelation of gossypol with Fe 2+ at molar ratio by 1:1, 1:3, and 1:4 respectively. Abstract : Five complexes of gossypol with Fe 2+ were obtained at 25 °C by using methanol as solvent in the presence of CO2 . Compound 2 and 3 were formed by coordination of gossypol with Fe 2+ at 1:2 molar ratio, compound 1, 4, and 5 were formed by chelation of gossypol with Fe 2+ at molar ratio by 1:1, 1:3, and 1:4 respectively.